Dermatology Centered Student Run Free Clinics: A Community Necessity - Rebecca Fliorent; Jensen Clark; Jiwoo Kim; Gillian McCarthy; Zachary Bloom; Samanatha Plasner; Nicole Castro (Journal of Student-Run Clinics, 2025)
Background: Student-run free clinics (SRFCs) play a crucial role in providing preventive healthcare and addressing disparities, especially in underserved communities. However, dermatologic care remains largely unavailable in SRFCs. This review examines the need for dermatology-centered SRFCs, evaluates current literature, and suggests ways to enhance dermatologic access for underserved populations, focusing on Camden County, New Jersey.Methods: A comprehensive literature review was conducted using PubMed, Embase, Cochrane, and Google Scholar databases to identify studies on dermatologic services in SRFCs and barriers to care, particularly for minority and uninsured populations.Results: The review identified limited availability of dermatologic services in SRFCs, with only a few successfully integrating dermatology clinics. Partnerships between SRFCs and dermatology departments have shown positive outcomes, such as reduced wait times, improved access to care for conditions like acne and skin cancers, and better early disease detection. Challenges include logistical barriers, financial limitations, and limited provider availability, with minority and uninsured patients most affected.Conclusion: The findings highlight an unmet need for dermatologic care within SRFCs. Collaborations between SRFCs and dermatology departments offer promise in improving care access and outcomes, enhancing medical education, and fostering community engagement. Establishing dermatology-focused SRFCs could address healthcare disparities and boost dermatologic health literacy in underserved communities. Further research is needed to assess the long-term impact of these initiatives on health outcomes.